Amoebic gill disease and host response in Atlantic salmon (Salmo salar L.): A review. (13th July 2020) - Marcos‐López, Mar; Rodger, Hamish D.
Abstract: Gill health is one of the main health challenges for Atlantic salmon ( Salmo salar L.) mariculture worldwide, and amoebic gill disease (AGD), caused by the marine ectoprotozoan Neoparamoeba perurans, is currently one of the most significant diseases in terms of prevalence and economic impact. This review describes the host response of Atlantic salmon to the disease, focusing on the pathological changes, immune response and mechanisms underlying the prominent epithelial proliferation and mucus hypersecretion occurring in affected fish. Health management strategies and risk factors are also discussed.